Spatial variability of gastroschisis in Canada, 2006–2011: An exploratory analysis - Bassil, Kate L. (Can J Public Health, 2016)
OBJECTIVES: Gastroschisis is a serious birth defect of the abdominal wall that is associated with mortality and significant morbidity. Our understanding of the factors causing this defect is limited. The objective of this paper is to describe the geographic variation in incidence of gastroschisis and characterize the spatial pattern of all gastroschisis cases in Canada between 2006 and 2011. Specifically, we aimed to ascertain the differences in spatial patterns between geographic regions and identify significant clusters and their location. METHODS: The study population included 641 gastroschisis cases from the Canadian Pediatric Surgery Network (CAPSNet) database, a population-based dataset of all gastroschisis cases in Canada. Cases were geocoded based on maternal residence. Using Statistics Canada live-birth data as a denominator, the total prevalence of gastroschisis was calculated at the provincial/territorial levels. Random effects logistic models were used to estimate the rates of gastroschisis in each census division. These rates were then mapped using ArcGIS. Cluster detection was performed using Local Indicators of Spatial Association (LISA). RESULTS: There is significant spatial heterogeneity of the rate of gastroschisis across Canada at both the provincial/territorial and census-division level. The Yukon, Northwest Territories and Prince Edward Island have higher overall rates of gastroschisis relative to other provinces/territories. Several census divisions in Alberta, Manitoba, Saskatchewan, Ontario, Northwest Territories and British Columbia demonstrated case “clusters”, i.e., focally higher rates in discrete areas relative to surrounding areas. CONCLUSIONS: There is clear evidence of spatial variation in the rates of gastroschisis across Canada. Future research should explore the role of area-based variables in these patterns to improve our understanding of the etiology of gastroschisis.